Composite negative electrode active material, preparation method thereof, negative electrode and secondary battery containing the same

By using composite materials of silicon-based core particles, outer carbon coating and single-wall carbon nanotubes in the negative electrode active material of lithium secondary batteries, the problem of rupture of silicon-based negative electrode active material due to volume expansion is solved, and higher life characteristics and capacity are achieved.

CN113939930BActive Publication Date: 2025-03-07LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080042267.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-07-26
Filing Date
2020-07-23
Publication Date
2025-03-07
Estimated Expiration
2040-07-23

AI Technical Summary

Technical Problem

The silicon-based negative electrode active material breaks the active material due to volume expansion/shrinkage during charging and discharging, reducing its life characteristics and capacity.

Method used

A composite negative electrode active material containing silicon-based core particles, an outer carbon coating and single-wall carbon nanotubes is used to form a conductive network through heat treatment to prevent electrical short circuits.

Benefits of technology

It effectively prevents electrical short circuits of active materials due to volume changes, and improves the life characteristics of the negative electrode and secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113939930B_ABST
    Figure CN113939930B_ABST
Patent Text Reader

Abstract

The present invention relates to a composite negative electrode active material, which comprises: a silicon-based core particle; an outer carbon coating layer formed on the silicon-based core particle; and a single-walled carbon nanotube, wherein the single-walled carbon nanotube is in contact with the outer carbon coating layer and comprises a main body partially separated from the outer carbon coating layer, and the outer carbon coating layer contains 35 wt % to 55 wt % of oxygen therein.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] This application claims priority to and the benefit of Korean Patent Application No. 10-2019-0091148, filed on Jul. 26, 2019, which is hereby incorporated by reference herein in its entirety. Technical Field

[0004] The invention relates to a composite negative electrode active material, a preparation method thereof, a negative electrode comprising the composite negative electrode active material and a secondary battery. Background Art

[0005] Recently, with the rapid popularization of electronic devices such as mobile phones, notebook computers and electric vehicles using batteries, the demand for secondary batteries with small size and light weight but relatively high capacity has been increasing sharply. In particular, lithium secondary batteries are light in weight and have high energy density, so they have become the focus as a driving power source for portable devices. Therefore, attempts to improve the performance of lithium secondary batteries have been actively carried out for research and development.

[0006] A lithium secondary battery generally comprises a positive electrode, a negative electrode, a separator disposed between the positive electrode and the negative electrode, an electrolyte, an organic solvent, etc. In addition, in the positive electrode and the negative electrode, an active material layer comprising a positive electrode active material or a negative electrode active material may be formed on the current collector. Generally, lithium-containing metal oxides such as LiCoO2, LiMn2O4, etc. are used as positive electrode active materials in the positive electrode, thereby using a lithium-free carbon-based active material or a silicon-based negative electrode active material as a negative electrode active material in the negative electrode.

[0007] In particular, among negative electrode active materials, silicon-based negative electrode active materials have attracted great attention because their capacity is about 10 times that of carbon-based negative electrode active materials, and they have the advantage of being able to achieve high energy density even with thin electrodes due to their high capacity. However, silicon-based negative electrode active materials are not widely used because of the following problems: volume expansion occurs due to charging and discharging, and active material particles are broken / damaged due to volume expansion, and thus, life characteristics are deteriorated.

[0008] In particular, the problem with silicon-based negative electrode active materials is that due to volume expansion / contraction caused by charging and discharging, the distance between active materials may increase and electrical short circuits may occur between active materials, and therefore, the charge movement path may be lost and lithium ions may be isolated, thereby reducing capacity and accelerating life degradation.

[0009] Therefore, there is a need to develop a secondary battery having improved lifespan characteristics while achieving high capacity and high energy density of a silicon-based negative electrode active material.

[0010] Korean Unexamined Patent Publication No. 10-2017-0074030 relates to a negative electrode active material for a lithium secondary battery, a preparation method thereof, and a lithium secondary battery including the same, and discloses a negative electrode active material including a porous silicon-carbon composite material, but there are still limitations in solving the above-mentioned problems.

[0011] Prior art literature

[0012] [Patent Document]

[0013] Korean Unexamined Patent Publication No. 10-2017-0074030 Summary of the invention

[0014] [Technical issues]

[0015] The present invention aims to provide a composite negative electrode active material which can effectively prevent electrical short circuits between active materials caused by charging and discharging and improve life characteristics when using a silicon-based active material.

[0016] The present invention also aims to provide a method for preparing the composite negative electrode active material.

[0017] The present invention also aims to provide a negative electrode and a secondary battery comprising the composite negative electrode active material.

[0018] [Technical solution]

[0019] One aspect of the present invention provides a composite negative electrode active material, which comprises a silicon-based core particle, an outer carbon coating formed on the silicon-based core particle, and a single-walled carbon nanotube, wherein the single-walled carbon nanotube is in contact with the outer carbon coating and comprises a main body partially separated from the outer carbon coating, and the outer carbon coating contains 35 wt % to 55 wt % of oxygen therein.

[0020] Another aspect of the present invention provides a method for preparing a composite negative electrode active material, the method comprising the steps of: mixing silicon-based core particles, a precursor for forming an outer carbon coating, and single-walled carbon nanotubes; and heat treating the mixture at 250°C to 650°C.

[0021] Another aspect of the present invention provides a negative electrode, comprising a negative electrode collector and a negative electrode active material layer formed on the negative electrode collector, wherein the negative electrode active material layer comprises a negative electrode material containing the above-mentioned composite negative electrode active material, a binder and a conductive material.

[0022] Still another aspect of the present invention provides a secondary battery including the above-mentioned negative electrode, a positive electrode facing the negative electrode, a separator provided between the negative electrode and the positive electrode, and an electrolyte.

[0023] [Beneficial Effects]

[0024] The composite negative electrode active material of the present invention comprises a silicon-based core particle, an outer carbon coating formed on the silicon-based core particle, and a single-walled carbon nanotube, wherein the single-walled carbon nanotube is in contact with the outer carbon coating and comprises a main body that is partially separated from the outer carbon coating, and the outer carbon coating comprises a specific content of oxygen. A portion of the single-walled carbon nanotube is attached to the outer carbon coating, and the remaining portion thereof that is not attached to the outer carbon coating is separated from the outer carbon coating and exposed to the outside of the composite negative electrode active material, so that the single-walled carbon nanotube can form a conductive network that prevents electrical short circuits between active materials, thereby preventing electrical short circuits between active materials even when the active materials expand / contract in volume due to charge and discharge. In addition, because part of the single-walled carbon nanotube is attached and fixed to the outer carbon coating, a conductive network can be uniformly and stably formed in the negative electrode, thereby improving the life characteristics of the negative electrode and the secondary battery.

[0025] In addition, according to the method for preparing a composite negative electrode active material of the present invention, a composite negative electrode active material is prepared by mixing silicon-based core particles, a precursor for forming an outer carbon coating layer, and single-walled carbon nanotubes, and then forming the mixture into a composite material within a specific temperature range. Therefore, the carbon coating layer can be prevented from being carbonized by heat treatment at an excessively high temperature, so that the single-walled carbon nanotubes can be attached to the carbon coating layer at an appropriate level, and can contribute to the formation of a conductive network between active materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 : is a scanning electron microscope (SEM) image showing the composite negative electrode active material of Example 1.

[0027] Figure 2 : is a SEM image showing the composite negative electrode active material of Example 2.

[0028] Figure 3 : is a SEM image showing the composite negative electrode active material of Comparative Example 1.

[0029] Figure 4 : is a SEM image showing the composite negative electrode active material of Comparative Example 2.

[0030] Figure 5 : is a SEM image showing the composite negative electrode active material of Comparative Example 4. DETAILED DESCRIPTION

[0031] The terms or words used in the present specification and claims should not be construed as limited to the ordinary or dictionary meanings, but should be construed as meanings and concepts consistent with the spirit of the invention on the basis of the principle that the inventor can appropriately define the concepts of the terms to describe the inventor's invention in the best manner.

[0032] The terms used in this specification are only used to describe specific various embodiments and are not intended to limit the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form as well.

[0033] It should be understood that the terms "comprising", "including" and / or "having" used in this document are used to clarify the existence of the described features, integers, steps, operations, elements, components and / or their combinations, but do not exclude the existence or addition of at least one other feature, integer, step, operation, element, component and / or its combination.

[0034] In this specification, the average particle size (D 50 ) can be defined as the particle size corresponding to 50% in the particle size distribution curve based on cumulative volume. The average particle size (D) can be measured using laser diffraction. 50 ). Laser diffraction can be used to measure particle sizes ranging from submicrometers to several millimeters, and can obtain results with high reproducibility and high resolution.

[0035] Hereinafter, the present invention will be described in detail.

[0036] <Composite negative electrode active material>

[0037] The present invention relates to a composite negative electrode active material, which can be preferably used in a lithium secondary battery.

[0038] The composite negative electrode active material of the present invention comprises: a silicon-based core particle; an outer carbon coating formed on the silicon-based core particle; and a single-walled carbon nanotube (hereinafter, referred to as "SWCNT"), wherein the SWCNT is in contact with the outer carbon coating and comprises a body partially separated from the outer carbon coating, and the outer carbon coating contains 35 wt % to 55 wt % of oxygen therein.

[0039] Generally, silicon-based negative electrode active materials are known to have a capacity of about 10 times that of carbon-based active materials, and therefore, when applied to negative electrodes, even low-thickness silicon-based negative electrode active materials are expected to achieve thin-film electrodes with high energy density levels. However, silicon-based negative electrode active materials have a problem of life degradation caused by volume expansion / contraction that occurs when lithium ions are intercalated / deintercalated with charging and discharging. In particular, when the silicon-based active material undergoes volume expansion / contraction due to charging and discharging, the distance between the active materials increases, causing the electrical contact between the active materials to decrease and an electrical short circuit to occur therebetween. As a result, the charge movement path may be lost and the lithium ions may be isolated, which may lead to rapid life degradation and reduced capacity of the negative electrode.

[0040] In order to solve these problems, the composite negative electrode active material of the present invention comprises a silicon-based core particle, an outer carbon coating formed on the silicon-based core particle, and a SWCNT, and the SWCNT is in contact with the outer carbon coating and comprises a main body that is partially separated from the outer carbon coating. Because a part of the main body of the SWCNT is separated from the outer carbon coating, a conductive network can be formed between the composite negative electrode active materials. Therefore, in the composite negative electrode active material of the present invention, even when the silicon-based core particle expands in volume due to charging and discharging, an electrical short circuit can be prevented due to the conductive network formed by the SWCNT, which is preferred in view of the life characteristics of the negative electrode and the reduction of resistance.

[0041] Furthermore, according to the present invention, since the SWCNTs are in contact with the outer carbon coating layer, when the composite negative electrode active material is included in the negative electrode, the SWCNTs may be uniformly arranged in the negative electrode, so that a uniform and stable conductive network may be formed in the negative electrode.

[0042] The silicon-based core particles are capable of intercalating / deintercalating lithium and can be used as core particles of a composite negative electrode active material.

[0043] The silicon-based core particles may include a compound represented by the following Formula 1,

[0044] [Formula 1]

[0045] M x SiO y

[0046] Wherein M may be at least one selected from the group consisting of Li, Mg and Al, 0≤x≤4, and 0≤y<2.

[0047] In Formula 1, y is preferably within the above range because SiO2 (in the case of x=0 and y=2 in Formula 1) does not react with lithium ions and thus cannot store lithium. Specifically, in Formula 1, considering the structural stability of the active material, y may be 0.5≤y≤1.5.

[0048] In Formula 1, in consideration of reducing the proportion of the irreversible phase (e.g., SiO2) of the silicon-based core particles to improve the efficiency of the active material, M may be contained, and M may be at least one selected from the following: Li, Mg, and Al, preferably, may be at least one selected from the following: Li and Mg.

[0049] The average particle size (D ) of the silicon-based core particles is 1.37×10 Å, which is smaller than 1.57×10 Å. ... 50 ) can be 1 μm to 10 μm, preferably 2 μm to 6 μm.

[0050] The content of the silicon-based core particles in the composite negative electrode active material may be 90 wt % to 99.9 wt %, preferably 92 wt % to 97 wt %. When the silicon-based core particles are contained within the above range, it is preferred in view of improving the capacity of the negative electrode, and the conductive network formed by SWCNT can be formed at a stable level, which will be described below, and thus it is preferred in view of preventing electrical short circuits caused by volume expansion of the active material and improving life characteristics.

[0051] The outer carbon coating layer is formed on the silicon-based core particles, can appropriately control volume expansion / contraction of the silicon-based core particles due to charge and discharge, and contains a portion of the SWCNTs attached thereto to form a composite material with the SWCNTs.

[0052] The outer carbon coating layer contains oxygen (O), and the content of oxygen in the outer carbon coating layer is 35 wt % to 55 wt %.

[0053] The outer carbon coating layer can be formed by mixing silicon-based core particles, SWCNTs, and a precursor for forming the outer carbon coating layer and heat-treating the mixture, and oxygen in the precursor for forming the outer carbon coating layer can be reduced by heat treatment. The composite negative electrode active material of the present invention is heat-treated to an appropriate level, thereby including an outer carbon coating layer in which the oxygen content is adjusted within the above range, so that a portion of the body of the SWCNTs exposed to the outside by being spaced apart from the outer carbon coating layer can make it possible to form a conductive network more uniformly and stably between the composite negative electrode active materials.

[0054] When the oxygen content in the outer carbon coating layer is less than 35 wt %, the outer carbon coating layer may be evaluated as being excessively carbonized by the heat treatment, and thus, it may be difficult to form a free and flexible conductive network by SWCNTs because SWCNTs may be excessively adsorbed or attached to or on the outer carbon coating layer. When the oxygen content in the outer carbon coating layer is greater than 55 wt %, the heat treatment level for forming the outer carbon coating layer is insufficient, and thus SWCNTs may not be fixed in the composite negative electrode active material at a desired level.

[0055] The content of oxygen in the outer carbon coating layer may be 40 wt % to 55 wt %, preferably 49 wt % to 52 wt %, and the content of oxygen within this range is preferred because the SWCNTs can be attached to the outer carbon coating layer in such a manner that a portion of the body of the SWCNTs is spaced apart from the outer carbon coating layer.

[0056] The oxygen content can be achieved by selecting the precursors used to form the outer carbon coating and controlling the heat treatment temperature.

[0057] The oxygen content in the outer carbon coating can be measured using X-ray photoelectron spectroscopy (XPS).

[0058] The content of the outer carbon coating layer in the composite negative electrode active material may be 0.001 wt % to 0.2 wt %, preferably 0.01 wt % to 0.1 wt %, more preferably 0.05 wt % to 0.078 wt %, and the amount of the outer carbon coating layer within this range is preferred because the SWCNTs can be sufficiently attached to the outer carbon coating layer in such a manner that a portion of the body of the SWCNTs is spaced apart from the outer carbon coating layer.

[0059] The SWCNT is in contact with the outer carbon coating, and a portion of the body of the SWCNT is spaced apart from the outer carbon coating. The outer carbon coating and the SWCNT are in contact with each other, and a portion of the body of the SWCNT is spaced apart from the outer carbon coating, while another portion of the body of the SWCNT may be attached or adsorbed to or on the outer carbon coating.

[0060] SWCNT is a carbon nanotube having a single cylindrical wall and a fiber shape. Compared with multi-walled carbon nanotubes (hereinafter referred to as "MWCNT"), SWCNT has a longer fiber length due to no breakage during the growth of the tube, and also has a higher degree of graphitization and higher crystallinity.

[0061] In the composite negative electrode active material of the present invention, a portion of the main body of SWCNT can be exposed to the outside by being spaced apart from the outer carbon coating, and since the fiber length of SWCNT is long, flexible, and highly crystallinity, a portion of the main body of SWCNT exposed to the outside can form a conductive network that contributes to the electrical contact between the composite negative electrode active materials. Therefore, in the composite negative electrode active material of the present invention, even if the active material undergoes volume expansion in the negative electrode due to charging and discharging, SWCNT can stably maintain electrical contact. Therefore, the composite negative electrode active material of the present invention is also preferred in view of the fact that the phenomenon that an electrical short circuit occurs due to the volume expansion of the active material and thus the life of the active material rapidly deteriorates can be effectively prevented, the life characteristics of the negative electrode can be improved, and the electrical contact between the active materials can be smoothly maintained due to SWCNT, so that the resistance can be reduced and the efficiency can be improved.

[0062] Furthermore, in the composite negative electrode active material of the present invention, since SWCNTs are in contact with the outer carbon coating, SWCNTs can be uniformly disposed between active materials and can form a uniform and stable conductive network in the negative electrode, compared with the case where the active material and SWCNTs are simply mixed.

[0063] The average length of the SWCNT may be 3 μm or more, preferably 4 μm or more, and more preferably 4.5 μm to 10 μm. The above range is preferred because a conductive network between active materials can be stably maintained.

[0064] In this specification, the average length of SWCNT is measured by the following method. A solution obtained by adding SWCNT and carboxymethyl cellulose (CMC) to water at a weight ratio of 40:60 (containing 1% by weight of solid content based on the total weight of the solution) is diluted 1000 times in water. Thereafter, 20 ml of the diluted solution is filtered through a filter, and the filter containing the SWCNT filtered thereon is dried. One hundred scanning electron microscope (SEM) images are taken from the dried filter, the length of SWCNT is measured using the ImageJ program, and the average value of the measured length is defined as the average length of SWCNT.

[0065] The average diameter of the SWCNT may be 0.1 nm to 15 nm, preferably 2 nm to 7 nm. When the average diameter of the SWCNT is within the above range, it is preferred in view of preventing the SWCNT from being cut and ensuring flexibility.

[0066] In this specification, the average diameter of SWCNT is measured by the following method. A solution obtained by adding SWCNT and carboxymethyl cellulose (CMC) to water at a weight ratio of 40:60 (containing 1% by weight of solid content based on the total weight of the solution) is diluted 1000 times in water. A drop of the diluted solution is dropped on a grid of a transmission electron microscope (TEM), and then the TEM grid is dried. The dried TEM grid is observed using a TEM device (H-7650 manufactured by Hitachi High-Tech Corporation), and the average diameter of SWCNT is measured.

[0067] The ratio of the average length of SWCNTs to the average diameter of SWCNTs may be in the range of 500:1 or greater, preferably 500:1 to 10,000:1, and more preferably 750:1 to 2,000:1, and the ratio within this range is preferred in consideration of the fact that SWCNTs may have high conductivity, may be prevented from breaking, and may have improved flexibility.

[0068] The content of SWCNT in the composite negative electrode active material can be 0.005 wt% to 0.2 wt%, preferably 0.015 wt% to 0.15 wt%, and more preferably 0.05 wt% to 0.12 wt%, and the amount of SWCNT within this range is preferred in view of the fact that the phenomenon that SWCNT and the active material are entangled and aggregated together due to excessive addition of SWCNT is prevented, and a conductive network can be formed more uniformly while sufficiently improving conductivity.

[0069] The composite negative electrode active material of the present invention may further include an inner carbon coating layer formed between the silicon-based core particles and the outer carbon coating layer. The inner carbon coating layer suppresses volume expansion of the silicon-based core particles and may serve as a protective layer to prevent side reactions with the electrolyte.

[0070] The content of the inner carbon coating in the composite negative electrode active material can be 1 wt % to 10 wt %, preferably 3 wt % to 7 wt %, and the amount of the inner carbon coating within this range is preferred in view of the fact that while the volume expansion of the silicon-based core particles is controlled to an excellent level, a side reaction between the inner carbon coating and the electrolyte can be prevented.

[0071] The content of the inner carbon coating layer may be 1 wt % to 10 wt %, preferably 3 wt % to 7 wt %, based on the weight of the silicon-based core particles and the inner carbon coating layer, and the amount of the inner carbon coating layer within this range is preferred in view of the fact that a side reaction between the inner carbon coating layer and the electrolyte can be prevented while controlling the volume expansion of the silicon-based core particles to an excellent level.

[0072] <Method for preparing composite negative electrode active material>

[0073] In addition, the present invention provides a method for preparing the composite negative electrode active material.

[0074] Specifically, the method for preparing the composite negative electrode active material of the present invention comprises the following steps: mixing silicon-based core particles, a precursor for forming an outer carbon coating layer, and SWCNT; and heat-treating the mixture at 250° C. to 650° C.

[0075] According to the method for preparing a composite negative electrode active material of the present invention, a composite negative electrode active material is formed by mixing silicon-based core particles, a precursor for forming an outer carbon coating layer, and SWCNTs and heat-treating the mixture within a specific temperature range, wherein the composite negative electrode active material has the following form: the outer carbon coating layer is formed on the silicon-based core particles, the SWCNTs are in contact with the outer carbon coating layer, and a portion of the body of the SWCNTs is separated from the outer carbon coating layer.

[0076] In addition, according to the preparation method, SWCNT and the outer carbon coating are in contact with each other, and a portion of the main body of the SWCNT can be exposed to the outside of the composite negative electrode active material by being spaced apart from the outer carbon coating. A portion of the SWCNT main body exposed to the outside can form a conductive network that improves the electrical contact between the composite negative electrode active materials. Another portion of the SWCNT main body that is not spaced apart from the outer carbon coating can be attached and fixed to the outer carbon coating, so that a conductive network can exist between the composite negative electrode active materials at a more stable and uniform level. Therefore, the problem of volume expansion caused by using silicon-based core particles as active materials and the problem of electrical short circuit and the resulting life degradation can be effectively prevented.

[0077] The method for preparing the composite negative electrode active material of the present invention comprises mixing silicon-based core particles, a precursor for forming an outer carbon coating layer, and SWCNT.

[0078] The types, characteristics and contents of silicon-based core particles and SWCNTs are described above.

[0079] The precursor for forming the outer carbon coating layer is a component capable of forming the outer carbon coating layer of the composite negative electrode active material.

[0080] The precursor for forming the outer carbon coating layer may be at least one selected from the group consisting of carboxymethyl cellulose (CMC), methyl cellulose (MC), hydroxypropyl cellulose (HPC), methyl hydroxypropyl cellulose (MHPC), ethyl hydroxyethyl cellulose (EHEC), methyl ethyl hydroxyethyl cellulose (MEHEC) and cellulose gum, and may preferably be carboxymethyl cellulose.

[0081] The method for preparing a composite negative electrode active material of the present invention may further include forming an inner carbon coating on the silicon-based core particles before the mixing operation. The inner carbon coating is formed on the silicon-based core particles to properly control the volume expansion of the silicon-based core particles caused by charging and discharging, and can be used as a protective layer capable of preventing side reactions with the electrolyte.

[0082] The formation of the inner carbon coating layer can be performed by a chemical vapor deposition (CVD) method, specifically, can be performed by a chemical vapor deposition (CVD) method using at least one hydrocarbon gas selected from methane, ethane, and acetylene. According to the method, the inner carbon coating layer can be formed on the silicon-based core particles at a uniform level, so that the volume expansion of the silicon-based core particles can be smoothly controlled, and the side reaction caused by the electrolyte can be prevented.

[0083] The formation of the inner carbon coating layer may be performed at 800°C to 1,100°C and preferably at 900°C to 1,000°C.

[0084] Additional description of the inner carbon coating is given above.

[0085] The method for preparing the composite negative electrode active material of the present invention comprises heat treating the mixture at 250°C to 650°C.

[0086] When the heat treatment temperature is lower than 250°C, the oxygen content in the outer carbon coating is too high, and SWCNTs are difficult to be fully fixed in the carbon coating, resulting in that the conductive network formed in the negative electrode may be uneven. When the heat treatment temperature is higher than 650°C, the carbon coating may be excessively carbonized, or SWCNTs may be excessively attached and fixed in the carbon coating, making it difficult to form a free and flexible conductive network through SWCNTs.

[0087] Preferably, the heat treatment temperature may be in the range of 350°C to 500°C, and considering the fact that the oxygen content in the outer carbon coating layer can be adjusted to a suitable level and the SWCNTs can be attached to the outer carbon coating layer while ensuring the flexibility of the SWCNTs, the heat treatment temperature is preferred within this range.

[0088] The heat treatment may be performed for 0.5 to 5 hours, preferably 0.7 to 2 hours, and the heat treatment time within this range is preferred in view of controlling the attachment or adsorption degree of SWCNTs to a desired level and controlling the oxygen content in the outer carbon coating to a suitable level.

[0089] According to the method for preparing a composite negative electrode active material of the present invention, oxygen in a precursor for forming an outer carbon coating layer can be reduced by heat treatment, and the outer carbon coating layer can be formed in such a way that a portion of SWCNT is attached and fixed to the precursor for forming the outer carbon coating layer. Specifically, the outer carbon coating layer may contain 35 wt % to 55 wt %, preferably 40 wt % to 55 wt %, and more preferably 49 wt % to 52 wt % of oxygen. When the oxygen content is within the above range, it is determined that a portion of SWCNT is appropriately attached and fixed in the outer carbon coating layer.

[0090] <Negative electrode>

[0091] The present invention also provides a negative electrode comprising the composite negative electrode active material.

[0092] Specifically, the negative electrode of the present invention comprises: a negative electrode current collector; and a negative electrode active material layer formed on the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode material, a binder and a conductive material, and the negative electrode material comprises the above-mentioned composite negative electrode active material.

[0093] There is no particular limitation on the negative electrode current collector, as long as it has high conductivity and does not cause chemical changes in the battery. Specifically, as the negative electrode current collector, copper, stainless steel, aluminum, nickel, titanium, calcined carbon; copper or stainless steel with a surface treated with carbon, nickel, titanium, silver, etc.; aluminum-cadmium alloy, etc. can be used.

[0094] The negative electrode current collector may generally have a thickness of 3 μm to 500 μm.

[0095] The negative electrode current collector may have fine concavoconvexities formed on its surface to improve the binding force of the negative electrode active material. For example, the negative electrode current collector may be used in various forms such as film, sheet, foil, net, porous body, foam, non-woven fabric, etc.

[0096] The negative electrode active material layer is formed on the negative electrode current collector.

[0097] The negative electrode active material layer may include a negative electrode material and a binder, and the negative electrode material includes the above-mentioned composite negative electrode active material.

[0098] The composite negative electrode active material may exhibit excellent capacity characteristics by being included in the negative electrode, and may contribute to improving life characteristics of the negative electrode due to SWCNTs included therein.

[0099] A description of the composite negative electrode active material is given above.

[0100] The negative electrode material may also include a carbon-based active material together with the above-mentioned composite negative electrode active material, which is more preferred for reducing resistance and improving efficiency because the volume expansion of the entire negative electrode material can be reduced due to the carbon-based active material, which has a low degree of volume expansion with charging and discharging, and the conductive network caused by SWCNTs in the composite negative electrode active material can surround the carbon-based active material.

[0101] The carbon-based active material may include at least one selected from artificial graphite, natural graphite, hard carbon, soft carbon, carbon black, acetylene black, Ketjen black, Super P, graphene, and fibrous carbon, and preferably includes at least one selected from artificial graphite and natural graphite.

[0102] Considering providing structural stability during charge and discharge and reducing side reactions with the electrolyte, the average particle size (D 50 ) can be 5μm to 35μm, preferably 10μm to 20μm.

[0103] Specifically, considering the improvement of capacity characteristics and cycle characteristics at the same time, the negative electrode material preferably contains both a composite negative electrode active material and a carbon-based active material, and in more detail, the negative electrode material preferably contains a composite negative electrode active material and a carbon-based active material in a weight ratio of 5:95 to 30:70 and more preferably 10:90 to 20:80. Considering the improvement of capacity characteristics and cycle characteristics at the same time, the above range is preferred.

[0104] The content of the negative electrode material in the negative electrode active material layer may be 80 wt % to 99 wt %, preferably 90 wt % to 98.5 wt %.

[0105] The negative electrode active material layer contains a binder.

[0106] In view of improving the electrode adhesion and imparting sufficient resistance to the volume expansion / contraction of the active material, the binder may include at least one selected from the following: styrene-butadiene rubber (SBR), nitrile rubber, acrylic rubber, butyl rubber, fluororubber, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl alcohol (PVA), polyacrylic acid (PAA), polyethylene glycol (PEG), polyacrylonitrile (PAN) and polyacrylamide (PAM). Preferably, the binder may include styrene-butadiene rubber in view of having high strength, excellent resistance to the volume expansion / contraction of the silicon-based negative electrode active material and imparting excellent flexibility to the binder to prevent the electrode from warping, bending, etc.

[0107] The content of the binder in the negative electrode active material layer may be 0.55 wt % to 10 wt %, and is preferably within this range in view of more effectively controlling volume expansion of the active material.

[0108] If necessary, the negative electrode active material layer may further include a conductive material. The conductive material may be used to improve the conductivity of the negative electrode, and any conductive material that does not cause chemical changes and has conductivity is preferably used. Specifically, the conductive material may include at least one selected from the following: natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide and polyphenylene derivatives, and preferably includes carbon black in view of achieving high conductivity.

[0109] The content of the conductive material in the negative electrode active material layer may be 0.5 wt % to 10 wt %.

[0110] Considering that the electrical contact with the components of the negative electrode material is enhanced due to the above-mentioned SWCNT and the like, the thickness of the negative electrode active material layer may be 30 μm to 100 μm, and preferably 40 μm to 80 μm.

[0111] The negative electrode may be manufactured by dispersing a negative electrode material, a binder, and a conductive material in a solvent for forming a negative electrode slurry on a negative electrode collector to prepare a negative electrode slurry, coating the negative electrode collector with the negative electrode slurry, and then drying and roll-pressing.

[0112] In consideration of promoting dispersion of components, the solvent used to form the negative electrode slurry may include at least one selected from the group consisting of distilled water, ethanol, methanol, and isopropyl alcohol, preferably distilled water.

[0113] <Secondary Battery>

[0114] The present invention provides a secondary battery comprising the negative electrode, specifically a lithium secondary battery.

[0115] Specifically, the secondary battery according to the present invention includes: the above-mentioned negative electrode; a positive electrode disposed to face the negative electrode; a separator disposed between the negative electrode and the positive electrode; and an electrolyte.

[0116] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector.

[0117] There is no particular limitation on the positive electrode current collector as long as it has high electrical conductivity and does not cause chemical changes in the battery. Specifically, as the positive electrode current collector, the following can be used: copper, stainless steel, aluminum, nickel, titanium, calcined carbon; copper or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc.; aluminum-cadmium alloy, etc.

[0118] The positive electrode current collector generally may have a thickness of 3 to 500 μm.

[0119] The positive electrode current collector may have fine irregularities formed on its surface to improve the binding force of the positive electrode active material. For example, the positive electrode current collector can be used in various forms such as film, sheet, foil, net, porous body, foam, non-woven fabric, etc.

[0120] The positive electrode active material layer may include a positive electrode active material.

[0121] The positive electrode active material is a compound capable of reversibly inserting and extracting lithium ions, and specifically may include a lithium-transition metal composite oxide containing lithium and at least one transition metal selected from nickel, cobalt, manganese, and aluminum, preferably a lithium-transition metal composite oxide containing lithium and a transition metal including nickel, cobalt, and manganese.

[0122] More specifically, the lithium-transition metal composite oxide may be a lithium-manganese-based oxide (such as LiMnO2, LiMn2O4, etc.), a lithium-cobalt-based oxide (such as LiCoO2, etc.), a lithium-nickel-based oxide (such as LiNiO2, etc.), a lithium-nickel-manganese-based oxide (such as LiNi 1-Y Mn Y O2 (where 0 < Y < 1), LiMn 2-Z Ni Z O4 (where 0 < Z < 2), etc.), a lithium-nickel-cobalt-based oxide (such as LiNi 1-Y1 Co Y1 O2 (where 0 < Y1 < 1), etc.), a lithium-manganese-cobalt-based oxide (such as LiCo 1-Y2 Mn Y2 O2 (where 0 < Y2 < 1), LiMn 2-Z1 Co Z1 O4 (where 0 < Z1 < 2), etc.), a lithium-nickel-manganese-cobalt-based oxide (such as Li(Ni p Co q Mn r1)O2 (where 0 < p < 1, 0 < q < 1, 0 < r1 < 1, p + q + r1 = 1) or Li(Ni p1 Co q1 Mn r2 )O4 (where 0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2, p1 + q1 + r2 = 2), etc.) or lithium-nickel-cobalt-transition metal (M) oxide (e.g., Li(Ni p2 Co q2 Mn r3 M s2 )O2 (where M is selected from: Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p2, q2, r3, and s2 are each the atomic fractions of the elements independent of each other, and 0 < p2 < 1, 0 < q2 < 1, 0 < r3 < 1, 0 < s2 < 1, p2 + q2 + r3 + s2 = 1), etc.), and the substances can be used alone or in a mixture of two or more of them. Among them, considering the improvement of the capacity characteristics and stability of the battery, the lithium-transition metal composite oxide can be LiCoO2, LiMnO2, LiNiO2, lithium-nickel-manganese-cobalt oxide (e.g., Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, etc.) or lithium-nickel-cobalt-aluminum oxide (e.g., Li(Ni 0.8 Co 0.15 Al 0.05 )O2, etc.), and considering the significant improvement effect caused by controlling the type and content ratio of the constituent elements forming the lithium-transition metal composite oxide, the lithium-transition metal composite oxide can be Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.5 Mn 0.3 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2 or Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, and the substances can be used alone or in a mixture of two or more of them.

[0123] In consideration of fully expressing the capacity of the positive electrode active material, the content of the positive electrode active material in the positive electrode active material layer may be 80 wt % to 99 wt %, preferably 92 wt % to 98.5 wt %.

[0124] The positive electrode active material layer may further include a binder and / or a conductive material in addition to the positive electrode active material described above.

[0125] The binder is a component that helps the active material to bind to the conductive material and to the current collector. Specifically, the binder may include at least one selected from the group consisting of polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber and fluororubber, and preferably includes polyvinylidene fluoride.

[0126] The content of the binder in the positive electrode active material layer may be 1 wt % to 20 wt %, preferably 1.2 wt % to 10 wt %, in consideration of sufficiently ensuring bonding between components such as the positive electrode active material.

[0127] Conductive materials can be used to promote and improve the conductivity of secondary batteries, and there is no particular limitation as long as it does not cause chemical changes and has conductivity. Specifically, the conductive material may include at least one selected from the following: graphite such as natural graphite, artificial graphite, etc.; carbon black materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, etc.; conductive fibers such as carbon fibers, metal fibers, etc.; conductive tubes such as carbon nanotubes, etc.; fluorocarbons; metal powders such as aluminum powder, nickel powder, etc.; conductive whiskers composed of zinc oxide, potassium titanate, etc.; conductive metal oxides such as titanium oxide, etc.; and polyphenylene derivatives, and in view of improving conductivity, preferably carbon black is included.

[0128] In view of sufficiently ensuring conductivity, the content of the conductive material in the positive electrode active material layer may be 1 wt % to 20 wt %, preferably 1.2 wt % to 10 wt %.

[0129] The thickness of the positive electrode active material layer may be 30 μm to 400 μm, preferably 50 μm to 110 μm.

[0130] The positive electrode may be manufactured by applying a positive electrode slurry including a positive electrode active material and optionally a binder, a conductive material, and a solvent for forming the positive electrode slurry onto a positive electrode collector, followed by drying and roll-pressing.

[0131] When the positive electrode active material and optional binder, conductive material, etc. are included, the solvent for forming the positive electrode slurry may include an organic solvent such as N-methyl-2-pyrrolidone (NMP) and the like and may be used in an amount suitable for achieving a preferred viscosity. For example, the solvent for forming the positive electrode slurry may be included in the positive electrode slurry in such a manner that the amount of solid content including the positive electrode active material and optional binder and conductive material is in the range of 50 wt % to 95 wt % and preferably 70 wt % to 90 wt %.

[0132] There is no particular restriction on the separator, as long as it is generally used in lithium secondary batteries to separate the negative electrode from the positive electrode and provide a path for the movement of lithium ions. In particular, it is preferred that the separator has low resistance to the movement of electrolyte ions and has excellent ability to impregnate electrolytes. Specifically, it is possible to use: a porous polymer film, for example, a porous polymer film formed by a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer; or a stacked structure having two or more layers thereof. In addition, conventional porous non-woven fabrics can be used, such as non-woven fabrics formed by high melting point glass fibers or polyethylene terephthalate fibers. In addition, in order to ensure heat resistance or mechanical strength, a coated separator comprising a ceramic component or a polymer material can be used, and can be selectively used in a single-layer or multilayer structure.

[0133] In addition, as the electrolyte used in the present invention, an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel polymer electrolyte, a solid inorganic electrolyte or a molten inorganic electrolyte that can be used in manufacturing a secondary battery can be used, but the present invention is not limited thereto.

[0134] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0135] There is no specific limitation on the organic solvent, as long as it can be used as a medium through which ions participating in the electrochemical reaction of the battery can migrate. Specifically, as the organic solvent, it is possible to use: ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone or ε-caprolactone; ether solvents such as dibutyl ether or tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene or fluorobenzene; carbonate solvents such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) or propylene carbonate (PC); alcohol solvents such as ethanol or isopropanol; nitrile solvents such as R-CN (R is a linear, branched or cyclic C2 to C20 hydrocarbon group and may contain a double bond, an aromatic ring or an ether bond); amide solvents such as dimethylformamide, etc.; dioxolane solvents such as 1,3-dioxolane, etc.; or sulfolane solvents. Wherein, preferably use carbonate solvent, and more preferably use the mixture of cyclic carbonate such as ethylene carbonate or propylene carbonate that can improve the charge and discharge performance of battery with high ion conductivity and high dielectric constant and linear carbonate compound (such as ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate etc.) with low viscosity.In this case, when mixing cyclic carbonate and chain carbonate with the volume ratio of about 1:1~about 1:9, electrolyte can show excellent performance.

[0136] There is no particular restriction on the lithium salt as long as it is a compound that can provide lithium ions for lithium secondary batteries. Specifically, as lithium salts, LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, LiB(C2O4)2, etc. can be used. The concentration of the lithium salt is preferably in the range of 0.1 to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has suitable conductivity and viscosity, thereby showing excellent electrolyte performance, and lithium ions can move efficiently.

[0137] The secondary battery can be manufactured by a conventional method of manufacturing a secondary battery, that is, by disposing a separator between the above-mentioned negative electrode and positive electrode and injecting an electrolytic solution.

[0138] The secondary battery according to the present invention can be used in the following fields: portable devices such as mobile phones, notebook computers, digital cameras, etc.; and electric vehicles such as hybrid electric vehicles (HEV), etc., and is particularly preferably used as a battery constituting a medium-sized to large-sized battery module. Therefore, the present invention also provides a medium-sized to large-sized battery module comprising the above-mentioned secondary battery as a unit cell.

[0139] Such a medium to large-sized battery module is preferably used for a power source of a device requiring high output and large capacity, such as an electric vehicle, an HEV, or a power storage device.

[0140] Hereinafter, embodiments of the present invention will be described in detail in a manner that enables those skilled in the art to easily implement the present invention. However, the present invention can be implemented in many different forms and is not limited to the embodiments described below.

[0141] Example

[0142] Example 1: Preparation of composite negative electrode active material

[0143] The silicon-based core particles SiO (average particle size (D 50 Chemical vapor deposition (CVD) was performed to form an inner carbon coating layer on the silicon-based core particles. The inner carbon coating layer was formed in an amount of 5 wt % relative to the total weight of the silicon-based core particles and the inner carbon coating layer.

[0144] The silicon-based core particles on which the inner carbon coating layer was formed, carboxymethyl cellulose as a precursor for forming the outer carbon coating layer, and SWCNT were mixed in a weight ratio of 99.83:0.102:0.068.

[0145] The average length of the SWCNTs was 5 μm, the average diameter was 5 nm, and the average length / average diameter was 1,000.

[0146] The mixture was heat-treated at 450° C. for 1 hour to prepare a composite negative active material of Example 1 having a form in which an outer carbon coating layer was formed on the inner carbon coating layer, the SWCNTs were in contact with the outer carbon coating layer, and a portion of a body of the SWCNTs was spaced apart from the outer carbon coating layer.

[0147] The average particle size of the composite negative electrode active material (D 50 ) is about 5 μm, and in the composite negative electrode active material, a weight ratio of silicon-based core particles on which an inner carbon coating is formed: an outer carbon coating: SWCNT is 99.87:0.06:0.07.

[0148] Example 2: Preparation of composite negative electrode active material

[0149] A composite negative electrode active material of Example 2 was prepared in the same manner as Example 1, except that the heat treatment temperature was 300°C.

[0150] The average particle size of the composite negative electrode active material (D 50 ) is about 5 μm, and in the composite negative electrode active material, a weight ratio of silicon-based core particles on which an inner carbon coating is formed: an outer carbon coating: SWCNT is 99.85:0.08:0.07.

[0151] Example 3: Preparation of composite negative electrode active material

[0152] The composite negative active material of Example 3 was prepared in the same manner as Example 1, except that the silicon-based core particles having the inner carbon coating layer formed thereon, the precursor for forming the outer carbon coating layer, and SWCNT were mixed in a weight ratio of 99.95:0.03:0.02.

[0153] The average particle size of the composite negative electrode active material (D 50 ) is about 5 μm, and in the composite negative electrode active material, a weight ratio of silicon-based core particles on which an inner carbon coating is formed: an outer carbon coating: SWCNT is 99.96:0.02:0.02.

[0154] Example 4: Preparation of composite negative electrode active material

[0155] The composite negative active material of Example 4 was prepared in the same manner as Example 1, except that the silicon-based core particles having the inner carbon coating layer formed thereon, the precursor for forming the outer carbon coating layer, and SWCNT were mixed in a weight ratio of 99.75:0.15:0.1.

[0156] The average particle size of the composite negative electrode active material (D 50 ) is about 5 μm, and in the composite negative electrode active material, a weight ratio of silicon-based core particles on which an inner carbon coating is formed: an outer carbon coating: SWCNT is 99.82:0.08:0.1.

[0157] Comparative Example 1: Preparation of composite negative electrode active material

[0158] A composite negative electrode active material of Comparative Example 1 was prepared in the same manner as in Example 1, except that the heat treatment temperature was 200°C.

[0159] The average particle size of the composite negative electrode active material (D 50 ) is about 5 μm, and in the composite negative electrode active material, a weight ratio of silicon-based core particles on which an inner carbon coating is formed: an outer carbon coating: SWCNT is 99.82:0.11:0.07.

[0160] Comparative Example 2: Preparation of composite negative electrode active material

[0161] A composite negative electrode active material of Comparative Example 2 was prepared in the same manner as in Example 1, except that the heat treatment temperature was 700°C.

[0162] The average particle size of the composite negative electrode active material (D 50) is about 5 μm, and in the composite negative electrode active material, a weight ratio of silicon-based core particles on which an inner carbon coating is formed: an outer carbon coating: SWCNT is 99.89:0.04:0.07.

[0163] Comparative Example 3: Preparation of composite negative electrode active material

[0164] The composite negative active material of Comparative Example 3 was prepared in the same manner as Example 1, except that MWCNT was used instead of SWCNT, and the silicon-based core particles having an inner carbon coating layer formed thereon, the precursor for forming an outer carbon coating layer, and MWCNT were mixed in a weight ratio of 98.75:0.75:0.5.

[0165] The average length of the MWCNTs was 3 μm, the average diameter was 20 nm, and the average length / average diameter was 150.

[0166] The average particle size of the composite negative electrode active material (D 50 ) is about 5 μm, and in the composite negative electrode active material, the weight ratio of the silicon-based core particles on which the inner carbon coating is formed: the outer carbon coating: the MWCNT is 99.1:0.4:0.5.

[0167] Comparative Example 4: Preparation of negative electrode active material

[0168] The negative active material of Comparative Example 4 was prepared by mixing the silicon-based core particles having the inner carbon coating layer formed thereon, carboxymethyl cellulose, and SWCNT used in Example 1 at a weight ratio of 99.83:0.102:0.068. In the case of the negative active material of Comparative Example 4, no heat treatment was performed, so that no outer carbon coating layer was formed.

[0169] Comparative Example 5: Preparation of negative electrode active material

[0170] The negative active material of Comparative Example 5 was prepared by mixing the silicon-based core particles having the inner carbon coating layer formed thereon, carboxymethyl cellulose, and SWCNT used in Example 1 at a weight ratio of 99.65:0.21:0.14. In the case of the negative active material of Comparative Example 5, no heat treatment was performed, so that no outer carbon coating layer was formed.

[0171] Here, the average length and average diameter of SWCNT or MWCNT were measured by the following method.

[0172] 1) Average length

[0173] A solution obtained by adding SWCNT (or MWCNT) and carboxymethyl cellulose (CMC) used in Examples and Comparative Examples to water at a weight ratio of 40:60 (containing 1% by weight of solid content based on the total weight of the solution) was diluted 1,000 times in water. Thereafter, 20 ml of the diluted solution was filtered through a filter, and the filter containing the SWCNT (or MWCNT) filtered thereon was dried. One hundred SEM images were taken from the dried filter, the length of the SWCNT was measured using the ImageJ program, and the average of the measured lengths was defined as the average length of the SWCNT.

[0174] 2) Average diameter

[0175] A solution obtained by adding SWCNT (or MWCNT) and carboxymethyl cellulose (CMC) used in Examples and Comparative Examples to water at a weight ratio of 40:60 (containing 1% by weight of solid content based on the total weight of the solution) was diluted 1,000 times in water. A drop of the diluted solution was dropped on a grid of a transmission electron microscope (TEM), and the TEM grid was then dried. The dried TEM grid was observed using a TEM apparatus (H-7650 manufactured by Hitachi High-Technologies Corporation), and the average diameter of the SWCNT was measured.

[0176] Experimental example

[0177] Experimental Example 1: SEM Observation

[0178] The appearance of each composite negative electrode active material prepared in Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 4 was observed using SEM.

[0179] The SEM images of the composite negative electrode active materials of Example 1, Example 2, Comparative Example 1, Comparative Example 2 and Comparative Example 4 are shown in sequence. Figures 1 to 5 middle.

[0180] refer to Figure 1 and 2 , it can be seen that, in the composite negative electrode active materials of Examples 1 and 2, a composite material of silicon-based core particles and SWCNTs is formed in such a manner that a portion of the main body of the SWCNTs is spaced apart from the outer carbon coating.

[0181] refer to Figure 3 , it can be seen that, in the composite negative electrode active material of Comparative Example 1, although a composite material of SWCNT and silicon-based core particles was formed, the heat treatment was insufficient, thereby not forming a composite material at an expected level, and the life characteristics were poor as described below.

[0182] refer to Figure 4It can be seen that SWCNTs excessively adhere to the silicon-based core particles in the composite negative electrode active material of Comparative Example 2. Thus, in the case of Comparative Example 2, it is considered difficult to form a conductive network by SWCNTs.

[0183] refer to Figure 5 , it can be seen that the SWCNTs are not attached to the silicon-based core particles but are dispersed because the negative electrode active material of Comparative Example 4 is not heat-treated during the preparation process.

[0184] Experimental Example 2 Measurement of oxygen content in the outer carbon coating

[0185] The depth profiles of X-ray photoelectron spectroscopy (XPS) of various composite negative electrode active materials in Examples 1 to 4 and Comparative Examples 1 to 3 were measured. Through the XPS depth profile, the boundary between the inner carbon coating and the outer carbon coating was distinguished according to the presence or absence of oxygen (O), and the oxygen content in the outer carbon coating was measured, and the results are shown in Table 1 below.

[0186] [Table 1]

[0187]

[0188] Referring to Table 1, it can be evaluated that in the composite negative active materials of Examples 1 to 4, the oxygen content in the outer carbon coating layer was adjusted to an appropriate level so that a composite material of silicon-based core particles and SWCNTs was formed at a desired level compared to Comparative Examples 1 and 2.

[0189] In Comparative Example 3, MWCNTs were used instead of SWCNTs, and the oxygen content in the outer carbon coating was adjusted to a suitable level, but as described below, the MWCNTs could not form a flexible and stable conductive network, and thus had poor life characteristics.

[0190] Experimental Example 3: Evaluation of Lifespan Characteristics

[0191] <Manufacturing of negative electrode>

[0192] The composite negative electrode active material prepared in Example 1 and natural graphite (average particle size (D 50 ):15μm) were mixed in a weight ratio of 15:85 to prepare the negative electrode material.

[0193] A negative electrode material, styrene butadiene rubber (SBR) as a binder, and carboxymethyl cellulose as a thickener were mixed at a weight ratio of 98:1:1, and the mixture was added to distilled water as a solvent for forming a negative electrode slurry to prepare a negative electrode slurry.

[0194] The negative electrode slurry was heated to 3 mAh / cm 2A loading amount of 1000 μm was applied to one surface of a copper current collector (thickness: 15 μm) as a negative electrode current collector, roll-pressed, and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 42 μm), and the obtained product was used as the negative electrode according to Example 1 (the thickness of the negative electrode was 57 μm and the area was 1.4875 cm 2 , and is circular).

[0195] Furthermore, negative electrodes of Examples 2 to 4 and Comparative Examples 1 to 5 were manufactured in the same manner as in Example 1, except that the composite negative electrode active materials of Examples 2 to 4 and Comparative Examples 1 to 5 were used instead of the composite negative electrode active material of Example 1, respectively.

[0196] <Manufacturing of Secondary Battery>

[0197] The usable area is 1.7671cm 2 And the circular lithium metal film is used as the positive electrode.

[0198] A polyethylene separator was placed between each of the negative electrodes prepared above and the positive electrode, and an electrolyte was injected to prepare a coin-type half-cell secondary battery.

[0199] An electrolyte was obtained by dissolving 0.5 wt % of vinylene carbonate (VC) and 1 M concentration of LiPF6 in a solution of ethyl methyl carbonate (EMC) and ethylene carbonate (EC) mixed in a volume ratio of 7:3.

[0200] <Evaluation of Capacity Retention Rate>

[0201] The cycle capacity retention ratio of each secondary battery prepared in Examples 1 to 4 and Comparative Examples 1 to 5 was evaluated using an electrochemical charge and discharge device.

[0202] The cycle capacity retention was measured by charging and discharging at 0.1 C for the first and second cycles, and charging and discharging at 0.5 C from the third cycle (charging conditions: constant current (CC) / constant voltage (CV), 5 mV / 0.005 C cutoff; discharging conditions: CC, 1.5 V cutoff).

[0203] The capacity retention rate was calculated using the following equation:

[0204] Capacity retention rate (%) = (discharge capacity at the Nth cycle / discharge capacity at the 1st cycle) × 100

[0205] (wherein N is an integer greater than or equal to 1).

[0206] The capacity retention (%) after 100 cycles is listed in Table 2 below.

[0207] [Table 2]

[0208]

[0209] Referring to Table 2, it can be seen that, compared with Comparative Examples 1 to 5, in the negative electrodes and secondary batteries using the composite negative electrode active materials of Examples 1 to 4, the cycle capacity retention ratio is improved to an excellent level.

Claims

1. A composite negative electrode active material, the composite negative electrode active material comprising: Silicon-based core particles; an outer carbon coating formed on the silicon-based core particle; and Single-walled carbon nanotubes, wherein the single-walled carbon nanotube is in contact with the outer carbon coating and comprises a body that is partially spaced apart from the outer carbon coating, and The outer carbon coating contains 35 wt % to 55 wt % oxygen therein, wherein the silicon-based core particles comprise a compound represented by the following Formula 1, [Formula 1] M x SiO y wherein M is one or more selected from the group consisting of Li, Mg and Al, 0≤x≤4, and 0 <y<2。 2 . The composite negative electrode active material according to claim 1 , further comprising an inner carbon coating layer formed between the silicon-based core particle and the outer carbon coating layer. 3 . The composite negative electrode active material according to claim 1 , wherein the single-walled carbon nanotubes have an average length of 3 μm or more. 4 . The composite negative electrode active material according to claim 1 , wherein the single-walled carbon nanotube has an average diameter of 0.1 nm to 15 nm. 5 . The composite negative electrode active material according to claim 1 , wherein the content of the single-walled carbon nanotubes in the composite negative electrode active material is 0.005 wt % to 0.2 wt %.

6. A method for preparing the composite negative electrode active material according to claim 1, the method comprising the following steps: mixing silicon-based core particles, a precursor for forming an outer carbon coating, and single-walled carbon nanotubes; and The obtained mixture is heat-treated at 250°C to 650°C.

7. The method according to claim 6, wherein the step of heat-treating the mixture is performed for 0.5 hour to 5 hours.

8. The method according to claim 6, wherein the precursor for forming the outer carbon coating layer comprises one or more selected from the group consisting of carboxymethyl cellulose, methyl cellulose, hydroxypropyl cellulose, methyl hydroxypropyl cellulose, ethyl hydroxyethyl cellulose and methyl ethyl hydroxyethyl cellulose.

9. The method according to claim 6, further comprising the step of forming an inner carbon coating on the silicon-based core particles before the mixing step.

10. The method according to claim 9, wherein the step of forming the inner carbon coating layer is performed by a chemical vapor deposition (CVD) method using one or more hydrocarbon gases selected from methane, ethane, and acetylene.

11. A negative electrode, comprising: a negative electrode current collector; and a negative electrode active material layer, wherein the negative electrode active material is formed on the negative electrode current collector, The negative electrode active material layer comprises a negative electrode material, a binder and a conductive material, and the negative electrode material comprises the composite negative electrode active material according to claim 1 .

12. The negative electrode according to claim 11, wherein The negative electrode material further comprises a carbon-based active material, and The negative electrode material includes the composite negative electrode active material and the carbon-based active material in a weight ratio of 5:95 to 30:

70.

13. A secondary battery, comprising: The negative electrode according to claim 11; a positive electrode facing the negative electrode; A separator disposed between the negative electrode and the positive electrode; and Electrolytes.

Citation Information

Patent Citations

  • Lighting control system and Ship having the same

    KR1020190091148A

  • Silicon carbon composite material for lithium ion battery and preparation method thereof

    CN108336317A

  • Negative active material for rechargeable lithium battery, method of preparing the same, and negative electrode and rechargeable lithium battery including the same

    KR1020130016727A